1965
DOI: 10.1002/jmor.1051170202
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of cardiac muscle in the pulmonary veins of rodentia

Abstract: Cardiac muscle fibers have been found to extend from me left auricle along the pulmonary veins as far as the hilus of the lungs in man, in dogs, and in rodents such as the guinea pig. In other rodents, however, the cardiac muscle extends into the veins of the lung itself. To study the occurrence of cardiac tissue in the pulmonary veins, the lungs of selected rodents which represent nine superfamilies have been examined. Only the guinea pig, Cavia porcellus, was limited to having cardiac muscle in the extrapulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 5 publications
3
21
0
Order By: Relevance
“…This tree subsequently enlarges in the following period to reach far into the smallest lung veins. 24 Taken together, between E10.5 and E12.5, a process of myocardium formation is observed around the pulmonary vein. Thereafter, this myocardial tree rapidly expands around the pulmonary vein branches.…”
Section: Development and Expression Analysis Of The Pulmonary Vein Mymentioning
confidence: 91%
“…This tree subsequently enlarges in the following period to reach far into the smallest lung veins. 24 Taken together, between E10.5 and E12.5, a process of myocardium formation is observed around the pulmonary vein. Thereafter, this myocardial tree rapidly expands around the pulmonary vein branches.…”
Section: Development and Expression Analysis Of The Pulmonary Vein Mymentioning
confidence: 91%
“…This tissue, named "pulmonary myocardium" (pm) by Favaro (Favaro, 1910), has been observed in numerous species including the shrew, mouse, rat, hamster, guinea pig, dog, deer, human, and bird (Kramer and Marks, 1965;Klika, 1976;Nathan and Gloobe, 1970;Endo et al, 1992a,b). Ultrastructural analyses showed that this muscle consists of striated mono-and bi-nucleate cells having narrow I-bands and intercalated discs and the sarcomere and single cell morphology are indistinguishable from cardiomyocytes (Karrer, 1959a,b;Ludatscher, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac muscle in the walls of extraptilmonary veins of a variety of rodents was first recognized by Rattschel [1836], as cited by Benninghoff[ 1930], Reviews of early studies have been made by Benninghoffl 1930], and more recently by Karrer [1959], Kramer and Marks [1966] and De Almeida et at. [1975].…”
Section: Introductionmentioning
confidence: 99%